A 31-Year-Old Man with Primary Hyperparathyroidism Due to Parathyroid Adenoma: A Case Report (Journal of Rangpur Medical College, 2024)
Primary hyperparathyroidism (PHPT) is an endocrine disorder characterized by chronic elevation of serum concentrations of calcium and parathyroid hormone (PTH).The most frequent forms of clinical presentation are symptomatic renal or skeletal disease with moderate or severe hypercalcemia. The biochemical profile of PHPT is characterized by hypercalcemia and high or inappropriately normal PTH concentrations. Parathyroidectomy is the only definitive cure. Medical treatment with the calcimimetic cinacalcet has been shown to normalize calcemia in a high percentage of cases. Our patient presented with recurrent vomiting, abdominal pain, electrolyte imbalance, renal impairment, bilateral nephrocalcinosis, hypercalcemia with high intact PTH, osteoporosis and right parathyroid adenoma and we go for surgical intervention.J Rang Med Col. September 2024; Vol. 9, No. 2: 94-97